A bacia do córrego limoeiro na perspectiva do índice de qualidade de água para proteção da vida aquática - SERRAGLIO, Rodolfo Durante (2020)
This scientific work aims to evaluate the quality of water resources according to the Índice de Qualidade de Água para Proteção da Vida Aquática - IVA (Water Quality Index for The Protection of Aquatic Life), in the Limoeiro Stream Basin, located in the municipalities of Presidente Prudente and Álvares Machado, SP. The Problematic seeks to answer the question: Did the interferences of anthropic action near the Limoeiro Stream Basin cause any environmental impact and/or damage? Methodologically, the actions of the Field Work were conducted, defining the 5 (five) strategic points, with the realization of two collection campaigns. Collections: 01 (March 30th, 2019 - rainy season) and 02 (August 21st, 2019 - dry period), samples were sent and analyzed by the Chemistry Laboratory of UNOESTE. The Results and Discussions present analytical and comparative data of the samples results, in direct interpretation with the scientific literature and the object of study observed conditions, which was found in the Limoeiro Stream through IVA, in the five points investigated and in the two periods that: in the Rainy Season presented a weighting coefficient of 4.1, considered "Regular" and in the Dry Period the index of 7.7 interpreted as "Terrible". Regarding IVA, inappropriate conditions for the maintenance of aquatic life were observed at the collection points, according to the standards indicated by the index and characterized by CETESB standards, such conditions were caused by possible anthropic activities, thus, the study shows that human action caused environmental impacts in the researched points.